Duration of dual anti-platelet therapy – State of the art after the DAPT and PEGASUS-TIMI 54 trials. Issue 3 (4th May 2017) - Pirlet, Charles; Legrand, Victor; Nyssen, Astrid; Pierard, Luc; Gach, Olivier
Abstract: Dual anti-platelet therapy is prescribed in the setting of coronary heart disease for the prevention of stent thrombosis and acute thrombotic events. The optimal duration of dual anti-platelet therapy is still under debate as numerous trials have shown non-inferiority of a strategy of early cessation of one of the agents as compared to the standard practice whereas two larger trials have demonstrated benefit of prolonging dual anti-platelet therapy.